MERCANTILE HOUSES AND CHEMISTS. APPROACHES TO THE DEVELOPMENT OF THE MEDICAL MARKETPLACE IN URBAN CHILE, 1860-1910 - Correa Gómez, María José (Revista de Historia Social y de las Mentalidades, 2024)
This article presents the Chilean medical marketplace from the late nineteenth and early twentieth centuries. Firstly, it examines the relationship between medicalization and commerce. Secondly, it shows some features of the urban medical marketplace through the international trade, the retail trade and the celebration of industrial production. It analyses the growth of the medical market and the diversification of therapeutics objects, and related them to the medicalization and urbanization processes of Chilean society.